Challenging Neuromuscular Disease Cases - Bodkin, Cynthia; Comer, Adam; Felker, Marcia; Gutmann, Laurie; Jones, Karra A.; Kincaid, John; Payne, Katelyn K.; Skinner, Blair (Seminars in Neurology, 2022)
The diagnosis of neuromuscular disorders requires a thorough history including family history and examination, with the next steps broadened now beyond electromyography and neuropathology to include genetic testing. The challenge in diagnosis can often be putting all the information together. With advances in genetic testing, some diagnoses that adult patients may have received as children deserve a second look and may result in diagnoses better defined or alternative diagnoses made. Clearly defining or redefining a diagnosis can result in understanding of potential other systems involved, prognosis, or potential treatments. This article presents several cases and approach to diagnosis as well as potential treatment and prognostic concerns, including seipinopathy, congenital myasthenic syndrome, central core myopathy, and myotonic dystrophy type 2.
Keywords: myopathy; congenital myasthenic syndrome; myotonic dystrophy; seipinopathy